Smoothing Tidal Effects in Well Test Pressure Data - de Oliveira, Felipe; Lins, Andréa; Barreto, Abelardo; Craizer, Marcos; Lopes, Hélio; Pesco, Sinesio (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
In petroleum reservoirs, parameters such as permeability, porosity, extension, and skin effects, have a high level of uncertainty. Different techniques attempt to improve the estimation of these parameters to improve production forecasting and cost reduction. The conventional production test, for example, requires the analysis of reservoir well pressure data. However, these data have several noise sources, such as the tidal effect, that may compromise the accuracy of test results. This letter proposes a method to smooth the noise generated by the tidal effect from well pressure data, using mathematical tools, such as the Fourier transform. We apply the discrete sine transform type I (DST-I) to filter the signal, and we use the pressure derivative to verify the results.